2021
DOI: 10.3390/toxins13020125
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Free and Conjugated Mycotoxins in Aromatic and Medicinal Plants and Dietary Exposure Assessment in the Moroccan Population

Abstract: Aromatic and medicinal plants (AMPs), as herbal material, are subjected to contamination by various mycotoxin-producing fungi, either free and conjugated. Such a problem is associated with poor storage practices, and lack of adopting good agricultural practices and good harvesting practices. Nevertheless, AMPs are poorly investigated. The purpose of this study was to investigate the co-occurrence of 15 mycotoxins (four aflatoxins (AFB1, AFB2, AFG1, and AFG2), ochratoxin A (OTA), beauvericin (BEA), four enniati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…However, no inference in the study was made to the risk associated with the ingestion of the raw medicinal plants. Similar results were reported on Moroccan aromatic and medicinal plants, whose infusions were shown not to pose an appreciable health risk owing to a low exposure, in spite of the fact that the concentrations of total AFs in some raw plant material exceed the regulatory standards of 4 ng/g or 10 ng/g [73]. It is worth mentioning that AFB 1 , the most toxic aflatoxin, whose carcinogenicity for humans is well established, was not detected in any of the samples analyzed in the latter study.…”
Section: Exposure Assessmentsupporting
confidence: 85%
“…However, no inference in the study was made to the risk associated with the ingestion of the raw medicinal plants. Similar results were reported on Moroccan aromatic and medicinal plants, whose infusions were shown not to pose an appreciable health risk owing to a low exposure, in spite of the fact that the concentrations of total AFs in some raw plant material exceed the regulatory standards of 4 ng/g or 10 ng/g [73]. It is worth mentioning that AFB 1 , the most toxic aflatoxin, whose carcinogenicity for humans is well established, was not detected in any of the samples analyzed in the latter study.…”
Section: Exposure Assessmentsupporting
confidence: 85%
“…A survey conducted between 2008 and 2017, which analyzed 74,821 feed and feed raw material samples from 100 countries worldwide, yielded interesting findings. The results indicated that the highest detection rates for ZEA and DON in finished feed and wheat samples were 48% and 28%, respectively, whereas DON had the second‐highest detection rate at 39% (El Jai et al., 2021). Notably, ZEA and DON were identified as the two most frequently co‐contaminated mycotoxins in feed samples from the Czech Republic during 2013–2017 and in winter rye samples from Poland during 2017–2018, with co‐detection rates of 56.63% and 83.3%, respectively (Svoboda et al., 2019; Zhang et al., 2021).…”
Section: Current Status Of Mycotoxin Joint Pollutionmentioning
confidence: 99%
“…4 In addition, it has been found in medicinal plants, including Curcuma longa and Acorus calamus , and other plants with crucial medicinal value. 5 ZEN poses a particular hazard in these plants when they are ingested as dietary supplements.…”
Section: Introductionmentioning
confidence: 99%